Assessing Hybridization Risk Between ESA-Listed Native Bull Trout (Salvelinus confluentus) and Introduced Brook Trout (S. fontinalis) Using Habitat Modeling - Manning, Michael A.; Arismendi, Ivan; Olivos, J. Andres; Giannico, Guillermo (Frontiers in Environmental Science, 2022)
The introduction of non-native species can negatively impact native species through reduced genetic fitness resulting from hybridization. The lack of spatiotemporal data of hybrid occurrences makes assessing hybridization risk difficult. Here, we developed a spatially-explicit Hybridization Risk Model (HRM) between native ESA-listed bull trout and introduced brook trout by combining an intrinsic potential model (IPM) of brook trout spawning habitat and existing empirical datasets of bull trout in Oregon, USA. We created an expert-based brook trout IPM classification score (0-1) of streams based on the potential of geophysical attributes (i.e., temperature, discharge, gradient, and valley confinement) to sustain spawning habitats. The HRM included a risk matrix based on the presence/absence of both species as well as the type of habitat (spawning versus other) at 100-m stream segment resolution. We defined that the hybridization risk was “extreme” when the respective stream reach contained bull trout spawning habitat and brook trout were present with IPM moderate or greater scores (IPM > 0.5). Conversely, “low” risk reaches contained historic or non-spawning bull trout habitat, brook trout were absent, and IPM scores were low (IPM < 0.25). Our HRM was able to classify 34 km of streams with extreme risk of hybridization, 115 km with high risk, 178 km with moderate risk, and 6,023 km with low risk. Our HRM can identify a differential risk of hybridization at multiple spatial scales when either both species coexist in bull trout spawning habitat or are absent. The model can identify stream reaches that would have higher risk of hybridization where brook trout are not currently present. Our modeling approach can be applied to other species, such as cutthroat trout and rainbow trout, Chinook and coho salmon, or similar species occurring elsewhere that potentially hybridize in freshwaters.